Enhancing Web Security Using AES and Twofish Algorithms - Ahmad Sahal; Farida Nur Aini; Zaidir Zaidir; Indra Listiawan (University of Respati Yogyakarta, Indonesia, 2025)
The advancement of information technology has driven the massive adoption of web-based information systems across various sectors. However, this surge in usage has been accompanied by increasingly complex data security threats, such as SQL injection attacks and sensitive information theft. This article proposes a security enhancement strategy through the implementation of encryption at the database and source code levels, focusing on the AES and Twofish algorithms. Web security, particularly through the use of the Advanced Encryption Standard (AES), plays a crucial role in safeguarding sensitive data across various applications. AES, especially in its 256-bit key variant (AES-256), is widely recognized for its robust security features, making it a preferred choice for encrypting data in cloud environments and web applications. The following sections highlight key aspects of AES in web security. The research findings that AES dan Twofish algorithms can provide an optimal balance between security and efficiency, making it a relevant solution for addressing information security challenges in the real application.